ANALISIS HUBUNGAN FAKTOR-FAKTOR YANG MEMILIKI KAITAN DENGAN TINGKAT KECENDERUNGAN LOYALITAS GURU DI KUPANG - Franky Franky; Zahera Mega Utama; Watriningsih Watriningsih (KELOLA: Jurnal Ilmiah Manajemen, 2022)
This study aims to find dominant factors that influence the level of loyalty of teachers at primary and secondary education levels in the city of Kupang, East Nusa Tenggara. Loyalty is a positive and constructive behavior for the development and progress of every organization. Workers who have high loyalty to their organizational units will make a positive contribution to the growth and development of the company or organization as a whole. This paradigm can also be implemented in the education sector. Teachers who have high loyalty will be the capital in developing school progress. This research uses quantitative methods. The population used is teachers at primary and secondary education who work in the city of Kupang. The number of samples used was 141 teachers. Data collection techniques using purposive sampling method. The analytical method used is Partial Least Square (PLS). The results of this study convey that there are 4 (four) factors that are significant dominant in building the behavior of teacher loyalty to educational institutions, especially in the city of Kupang. These factors are integrity, discipline towards school rules, coworkers, and income or salary.